Technology, innovation, and enterprise transformation - Wadhwa, Manish, 1981-; Harper, Alan H., 1966- (A volume in the advances in business information systems and analytics (ABISA) books series., 2015)
"This book addresses the crucial relationship between a business and its technical implementations, and how current innovations are changing how the industry operates by highlighting current theoretical frameworks, novel empirical research discoveries, and fundamental literature surveys"--